Troponin I, A Biomarker of Diagnosis of SIRS, Sepsis and Septic Shock - Afroza, Shahnaz; Begum, Muslema; Chowdhury, Iqbal Hossain; Hossain, Md Mozaffer (Journal of the Bangladesh Society of Anaesthesiologists, 2018)
Background: Sepsis related troponin elevation (SRTE) has always been the demand and supply mismatchtheory. In the setting of sepsis, the cardiac metabolic requirements are high and in order to meet theserequirements an increase in the coronary blood flow is needed. Patients with underlying anemia andpreexisting subclinical CAD may develop a mismatch ischemia in this setting. It was always thought thatsepsis-related hypotension causes a decrease in coronary perfusion pressure thus leading to a decreasedblood flow to cardiac myocytes and thereby leading to SRTE. Objectives: To establish Troponin-I as a useful diagnostic marker for sepsis. Settings and Study Design: This prospective study was carried out in the department of Anesthesia,pain, palliative and intensive care medicine, Dhaka Medical College, Dhaka during July 2013 to June2015. Methods: This study was carried out in the department of Anesthesia, pain, palliative and intensive caremedicine, Dhaka Medical College, Dhaka during July 2013 to June 2015. According to Troponin-I valuepatients were divided into Troponin-I positive and negative for sepsis. Three cut off values of Troponin-I(0.05, 0.035, 0.015) were used for this study. By using Receiver operating characteristic (ROC) curve thebest sensitively, specificity, negative predictive value and positive predictive values of Troponin-I weredetermined. Results: The validity of troponin I (>0.05 ng/dl) evaluation for blood culture positive were sensitivity45.0%, specificity 53.8%, accuracy 48.5%, positive predictive values 60.0% and negative predictive values38.9%. The validity of troponin I (>0.035 ng/dl) evaluation for blood culture positive were sensitivity57.5%, specificity 23.1%, accuracy 43.9%, positive predictive values 53.5% and negative predictive values26.1%. The validity of troponin I (>0.015 ng/dl) evaluation for blood culture positive were sensitivity72.5%, specificity 15.4%, accuracy 50.0%, positive predictive values 56.9% and negative predictive values26.7%. Conclusion: The cutoff values of troponin-I (>0.035 ng/dl) observed more sensitivity of blood culture. JBSA 2018; 31(1): 3-11